ANALISIS PENERAPAN MODEL INQUIRY DALAM PEMBELAJARAN MATEMATIKA DI SLB 4 JAKARTA - Yoga Pratama; Gelar Dwirahayu; Gusni Satriawati (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2020)
The Extraordinary School (SLB) 4 Jakarta is a school special for deafness students. The deafness students has a difference with a normal students, so there are special treatment for them especially in mathematics teaching. When we observe to school, we get some information about they services to students, one of the information was that the mathematics teacher taught students using inquiry model. Therefore, the purpose of this study is to analyze the application of mathematics learning models in SLBN 4 Jakarta for class XI students with hearing impairment in terms of planning and implementing learning, student responses and test results during the learning process, as well as the learning tools or media used. This research is a qualitative descriptive study with research subjects namely one mathematics class teacher and five students of SLBN 4 Jakarta class XI in the 2018/2019 school year. The collection techniques used were interviews, observation, and documentation. The results showed that (1) The preparation of mathematics learning planning in SLBN 4 Jakarta curriculum used was the 2013 curriculum (2) The implementation of mathematics learning in SLBN 4 Jakarta used the expository method and MMR (Reflective Maternal Method) (3) There were 2 results of learning activities, namely student responses and test results (4) mathematics learning tools or media used by teachers are still conventional.